1993
DOI: 10.1002/bem.2250140506
|View full text |Cite
|
Sign up to set email alerts
|

Effects of 60 Hz electric and magnetic fields on maturation of the rat neopallium

Abstract: This study was undertaken to determine the effects of extremely low frequency (ELF; 60 Hz) electromagnetic (EM) fields on somatic growth and cortical development, as well as biochemical and morphological maturation, of the rat neopallium. On the fifth day of pregnancy, female rats were put in pairs into plastic cages that were housed in a specially constructed apparatus for irradiation under three separate sets of combination and intensity: 1) 1 kV/m and 10 gauss; 2) 100 kV/m and 1 gauss; and 3) 100 kV/m and 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1995
1995
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
(1 reference statement)
0
5
0
Order By: Relevance
“…A few studies have been conducted to assess postnatal effects of in utero exposure to ELF fields. Although some changes have been reported in performing an operant task [Salzinger et al, 1990], territorial scent-marking behavior and accessory sex organ weights [McGivern et al, 1990], and brain DNA, RNA, and protein concentrations after combined electric and magnetic field exposures Yu et al, 1993], the results generally show no gross impairment of postnatal development or behavior. Effects of a 50 Hz, 20 mT magnetic field on postnatal development and behavior of prenatally exposed CD1 mice were studied by Sienkiewicz et al [1994].…”
Section: Magnetic Fields: Mammalian Speciesmentioning
confidence: 97%
“…A few studies have been conducted to assess postnatal effects of in utero exposure to ELF fields. Although some changes have been reported in performing an operant task [Salzinger et al, 1990], territorial scent-marking behavior and accessory sex organ weights [McGivern et al, 1990], and brain DNA, RNA, and protein concentrations after combined electric and magnetic field exposures Yu et al, 1993], the results generally show no gross impairment of postnatal development or behavior. Effects of a 50 Hz, 20 mT magnetic field on postnatal development and behavior of prenatally exposed CD1 mice were studied by Sienkiewicz et al [1994].…”
Section: Magnetic Fields: Mammalian Speciesmentioning
confidence: 97%
“…Therefore, GAP-43 may be a good biological marker for development and growth stimulation of cells in brain tissues. It has been reported that electromagnetic fields can alter biological cell proliferation [Heredia-Rojas et al, 2001], but exposure to electromagnetic fields does not seem to cause changes in somatic growth and cerebral development [Yu et al, 1993]. There has been only one article reporting the effect of exposure to an ELFMF on GAP-43 transcription, in which the magnetic field at a density of 2, 200, and 1000 mT did not affect the GAP-43 expression in rat brain tissues in vivo [Harry et al, 2000].…”
Section: Discussionmentioning
confidence: 98%
“…Consistent with these findings, the application of simple invariant (“temporally symmetric”) field patterns, such as sinusoidal or rectangular pulses, are generally ineffective in altering prenatal development unless much higher intensities are used. This important distinction between the waveform pattern and field strength could account for some of the contradictory evidence presented in the literature concerning the teratogenic effects of magnetic field exposure on foetal CNS development (Juutilainen et al, 1986; Ubeda et al, 1983; Wiley et al, 1992; Yu et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…presented in the literature concerning the teratogenic effects of magnetic field exposure on foetal CNS development (Juutilainen et al, 1986;Ubeda et al, 1983;Wiley et al, 1992;Yu et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation